2003
DOI: 10.1002/star.200300172
|View full text |Cite
|
Sign up to set email alerts
|

Role of Amylose in the Maintenance of the Configuration of Rice Starch Granules

Abstract: Amylose contents in 39 strains of rice starch, including waxy starch, low amylose containing starch, and non‐waxy starch, were measured. Seguchi et al. [1] reported that waxy wheat starch exhibits a ghost appearance by staining and swelling with 25% KI/10%I2 solution at 25 °C. We subjected the 39 rice strains to staining in the same manner. We found that the relative ghost area (%) in a rice starch, which is a measure of granule swelling in 25%KI/10%I2 solution, , is related to its amylose content (r = ‐0.78).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 8 publications
2
23
0
2
Order By: Relevance
“…This ghost phenomenon of the waxy wheat starch granule in concentrated KI/ I 2 solution has also been observed in waxy barley, rice, maize, proso millet, and foxtail millet starch granules [2]. The importance of the role of the amylose molecule in the stability of barley and rice starch granules was reported by Yasui et al [3] and Seguchi et al [4], respectively. However, waxy wheat starch granules have a peculiar nature, showing a remarkable double structure in the ghost, that is, a black-brown central portion and red-brown surrounding portion [1].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…This ghost phenomenon of the waxy wheat starch granule in concentrated KI/ I 2 solution has also been observed in waxy barley, rice, maize, proso millet, and foxtail millet starch granules [2]. The importance of the role of the amylose molecule in the stability of barley and rice starch granules was reported by Yasui et al [3] and Seguchi et al [4], respectively. However, waxy wheat starch granules have a peculiar nature, showing a remarkable double structure in the ghost, that is, a black-brown central portion and red-brown surrounding portion [1].…”
Section: Introductionsupporting
confidence: 59%
“…It was suggested that waxy wheat strains could have a synthesizing ability to produce amylopectin, and a minor amylose content was present in the A-type granules, however, in the B-type granule-biosynthesis system the ability to produce amylose was completely lost. This was supported by the fact that the amylose content in waxy rice starch granules showing a simple sack form such as wheat B-type starch granules was 0% [4].…”
Section: Resultsmentioning
confidence: 89%
“…The amylose content and the proportion of outside-chains of amylopectin were thought to be the major factors stabilizing the gel structure to retain water (Tang et al 2005). The distribution of amylose in starch granule was not uniform (Seguchi et al 2003), which also affect the swelling power of starch. The starch granules mainly contained amylose and amylopectin, during gelatinization, some amylose molecule leaked out; however, the quantity of amylose which leaked out was related to the channels and molecule structure or hydrogen bonding.…”
Section: Swelling Powermentioning
confidence: 99%
“…On the other hand, the distribution of amylose and amylopectin in starch granules also influence the solubility of starch. The amylose played a role in the maintenance of the structure of starch granules and concentrated in the central region of the granules (Seguchi et al 2003). Therefore, the higher amylose content, the more compact starch granule, the starch is more difficult to overflow outside the granules and lower solubility values.…”
Section: Solubilitymentioning
confidence: 99%
“…Seguchi et al . () have shown 39 kinds of RSs that were waxy, low amylose and nonwaxy, respectively. The samples exhibited a complete light brown color of their ghost structure in the absence of amylose.…”
Section: Resultsmentioning
confidence: 99%